When coronary anomalies induce arrhytmias: A case of ventricular tachycardia due to left coronary artery-pulmonary artery fistula - Saerang, Gebryel Dennis; Rizal, Ardian; Karolina, Wella (Universitas Brawijaya, 2025)
Background: Coronary artery fistula (CAF) is a rare vascular anomaly involving an abnormal connection between a coronary artery and another cardiac or vascular structure. Although often asymptomatic, CAF can cause myocardial ischemia, presenting as angina, dyspnea, or ventricular arrhythmias, due to flow diversion, leading to a coronary stealing phenomenon that poses a serious clinical challenge. Case: An 81-year-old female presented with chest pain, palpitations, and syncope. Electrocardiography (ECG) showed monomorphic VT, successfully cardioverted and managed with amiodarone. Following initial stabilization, she experienced recurrent episodes of VT that were terminated with lidocaine. Physical examination revealed a continuous machinery murmur at the left upper sternal border. Transthoracic echocardiography showed left coronary artery dilation with turbulent flow into the pulmonary artery. Aortography and coronary angiography confirmed a dilated left main coronary artery with an aneurysmal segment and a tortuous fistulous tract to the pulmonary artery. Computed tomography coronary angiography (CTCA) with 3D reconstruction confirmed a left coronary artery fistula to the pulmonary artery. Conclusion: This case highlights CAF as an uncommon yet clinically important etiology of recurrent VT, likely attributable to the coronary stealing phenomenon. Multimodal imaging, especially CTCA, is crucial for diagnosis and treatment planning. In addition to immediate management with cardioversion/defibrillation and antiarrhythmic drugs, treatment of ischemia as the underlying cause is important in the management of ischemia-induced VT. CAF closure is recommended in symptomatic or hemodynamically significant CAF to alleviate ischemic symptoms and prevent complication.